Incidence and prevalence of epilepsy in the Republic of North Macedonia: Data from nationwide integrated health care platform - Babunovska, Marija; Boskovski, Bojan; Kuzmanovski, I; Isjanovska, Rozalinda; Kiteva Trencevska, Gordana; Cvetkovska, Emilija (Elsevier BV, 2021)
This study aimed to evaluate the incidence and period prevalence of epilepsy in the Republic of North Macedonia, an upper-middle-income country with universal access to healthcare, based on a nationwide healthcare platform (NHP).